Genome‐wide identification and characterization of Eutrema salsugineum microRNAs for salt tolerance. Issue 4 (25th May 2016) - Wu, Ying; Guo, Jing; Cai, Yimei; Gong, Xiaolin; Xiong, Xuemei; Qi, Wenwen; Pang, Qiuying; Wang, Xumin; Wang, Yang
Abstract : Eutrema salsugineum, a close relative of Arabidopsis thaliana, is a valuable halophytic model plant that has extreme tolerance to salinity. As posttranscriptional gene regulators, microRNAs (miRNAs) control gene expression and a variety of biological processes, including plant‐stress responses. To identify salt‐stress responsive miRNAs in E. salsugineum and reveal their possible roles in the adaptive response to salt stress, we chose the Solexa sequencing platform to screen the miRNAs in 4‐week‐old E. salsugineum seedlings under salt treatment. A total of 82 conserved miRNAs belonging to 27 miRNA families and 17 novel miRNAs were identified and 11 conserved miRNA families and 4 novel miRNAs showed a significant response to salt stress. To investigate the possible biological roles of miRNAs, 1060 potential targets were predicted. Moreover, 35 gene ontology (GO) categories and 1 pathway, including a few terms that were directly and indirectly related to salt stress, were significantly enriched in the salt‐stress‐responsive miRNAs targets. The relative expression analysis of six target genes was analyzed using quantitative real‐time polymerase chain reaction (PCR) and showed a negative correlation with their corresponding miRNAs. Many stress regulatory and phytohormone regulatory cis ‐regulatory elements were widely present in the promoter region of the salt‐responsive miRNA precursors. This study describes the large‐scale characterization of E. salsugineum miRNAs and provides a useful resource for further understanding of miRNA functions in the regulation of the E. salsugineum salt‐stress response.